Whatever the odds : the incredible story behind DLF - Singh, K.P. (Noida Harper Collins)
The DLF saga has few rivals in the realty sector. Starting from Delhi, where the company developed the city's major residential colonies, the developer's focus shifted to Gurgaon in the 1970s, transforming a small town into a city of skyrises that is now an international business hub and a destination for young professionals to stay and work. Extraordinary as the story is, that of the man behind the revival and enormous success of the company is even more so, covering a journey from a small town in Uttar Pradesh to England where he became a part of high society, to a return to India and an army career en route to taking charge of DLF. From the small detail to the big picture, nothing is missing in this riveting account of conducting business in India in a politically charged atmosphere. As too of his own life with all its challenges and triumph over odds that would have defeated most people.
Keywords: Real estate developers; India